SARGASSUM POLYCYSTUM METHANOL EXTRACT AFFECTS THE NUCLEAR FACTOR-k BETA AND INTERLEUKIN-6 EXPRESSION IN STREPTOZOTOCIN-INDUCED DIABETES RATS - Firdaus, Muhamad; Chamidah, Anies (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to investigate the attenuation of the nuclear factor-Îº beta (NF-ÎºB) and interleukin (IL)-6 expression in streptozotocin-induced diabetic rats by Sargassum polycystum methanol extract. Methods: Diabetic rats were intraperitoneally induced by streptozotocin (40 mg/kg b.w.). S. polycystum methanol extract was administered to diabetic rats for 45 days. The effect of S. polycystum methanol extract on blood glucose, hemoglobin A1c (HbA1c), NF-ÎºB, and IL-6 expression was investigated on streptozotocin-induced diabetic rats. The gliclazide (30 mg/kg b.w., p.o.) was used as a reference antidiabetic drug. Results: The administration of S. polycystum methanol extract on streptozotocin-induced diabetic rats decreased the blood glucose level, HbA1c, NF-ÎºB, and IL-6. Conclusion: S. polycystum methanol extract indicates a promising anti-inflammation agent in diabetes.